Virtual fracture clinics: be vigilant for the ligamentous elbow injury. Issue 12 (17th December 2022) - Robertson-Waters, Eve E; Cuthbert, Rory; Van Rensburg, Lee
Abstract: The Covid-19 pandemic encouraged remote healthcare and led to dependency on virtual fracture clinics (VFC). VFC are orthopaedic consultant-led clinics where cases are reviewed virtually following referral by emergency department clinicians. Success is contingent on a comprehensive initial history and examination. This pathway has high patient satisfaction rates and cost-saving benefits. However, clinicians must be vigilant for high-energy mechanisms or examination findings suggestive of greater underlying injury. In this case, VFC missed a rare ipsilateral annular ligament injury in a 15-year old with an undisplaced radial neck fracture, following a fall from a horse. This led to radial head dislocation and delayed surgical repair. Untreated, radial head dislocations lead to pain and reduced range of movement. Despite the rarity of this injury pattern, face-to-face orthopaedic examination would have raised concern for significant ligamentous injury. A high-energy mechanism of injury mandates face-to-face senior orthopaedic review to avoid missing serious concomitant injury.